Effect of rare earth on structural, morphological, vibrational, magnetic and dielectric properties of RFe0.5Cr0.5O3 (R = Nd, Eu) perovskites. (July 2022) - Boudad, L.; Taibi, M.; Belayachi, W.; Abd-Lefdil, M.; Sajieddine, M.
Abstract: RFe0.5 Cr0.5 O3 (R = Nd, Eu) perovskites were synthesized through solid-state reaction. The structural analysis evidences the orthorhombic symmetry of these materials in accordance with their tolerance factor. The lattice parameters, bond lengths, and bond angles, as obtained by Rietveld refinement, vary systematically with the size of R 3+ cations. The structural stability and thermally activated expansion of the crystal lattice are affirmed by means of a high-temperature X-ray diffraction (HT-XRD) study. The microstructure of the prepared powders is investigated using scanning electron microscopy (SEM), as well as X-ray diffraction (XRD) through the calculation of the crystallite size. Diffuse reflectance spectra indicate that these materials behave as semiconductors, and the gap energies are calculated. Room-temperature Mössbauer spectroscopy highlights the presence of magnetic frustration phenomenon in both materials. The frequency-dependent dielectric study reveals a colossal dielectric constant in agreement with the Maxwell-Wagner relaxation mechanism resulting from intergrain boundaries, as asserted by impedance spectroscopy. The conductivity mechanism is provided by the correlated barrier hopping model for EuFe0.5 Cr0.5 O3 perovskite, and the non-overlapping small polaron tunneling mechanism for NdFe0.5 Cr0.5 O3 material. High-temperature dielectric measurements reveal two anomalous features attributed to the magnetodielectric effect and the onset of ferroelectric-paraelectric transition, respectively. Metallic behavior is identified at higher temperatures for both materials. Highlights: The RFe0.5 Cr0.5 O3 materials represent a Pbnm orthorhombic structure. The expansion of the crystal lattice at high temperatures and the effect of the R 3+ cations size on the structural distortion are discussed. Optical study highlighted a direct-band-gap of 1.90eV(NdFe0.5 Cr0.5 O3 ) and 1.98eV(EuFe0.5 Cr0.5 O3 ). Mossbauer spectroscopy revealed the onset of magnetic frustration resulting from the random distribution of Fe/Cr atoms. Both materials represent a Maxwell-Wagner relaxation related to the heterogeneous electrical response, as asserted by impedance spectroscopy. The temperature-dependent dielectric study suggests the presence of multiferroїc feature.